A Carbohydrate-Binding Protein from the Edible Lablab Beans Effectively Blocks the Infections of Influenza Viruses and SARS-CoV-2 - Liu, Yo-Min; Shahed-Al-Mahmud, Md; Chen, Xiaorui; Chen, Ting-Hua; Liao, Kuo-Shiang; Lo, Jennifer M.; Wu, Yi-Min; Ho, Meng-Chiao; Wu, Chung-Yi; Wong, Chi-Huey; Jan, Jia-Tsrong; Ma, Che (Cell reports (Cambridge), 2020)
The influenza virus hemagglutinin (HA) and coronavirus spike (S) protein mediate virus entry. HA and S proteins are heavily glycosylated, making them potential targets for carbohydrate binding agents such as lectins. Here, we show that the lectin FRIL, isolated from hyacinth beans (Lablab purpureus), has anti-influenza and anti-SARS-CoV-2 activity. FRIL can neutralize 11 representative human and avian influenza strains at low nanomolar concentrations, and intranasal administration of FRIL is protective against lethal H1N1 infection in mice. FRIL binds preferentially to complex-type N-glycans and neutralizes viruses that possess complex-type N-glycans on their envelopes. As a homotetramer, FRIL is capable of aggregating influenza particles through multivalent binding and trapping influenza virions in cytoplasmic late endosomes, preventing their nuclear entry. Remarkably, FRIL also effectively neutralizes SARS-CoV-2, preventing viral protein production and cytopathic effect in host cells. These findings suggest a potential application of FRIL for the prevention and/or treatment of influenza and COVID-19. [Display omitted] •FRIL is a plant lectin with potent anti-influenza and anti-SARS-CoV-2 activity•FRIL preferentially binds to complex-type N-glycans on viral glycoproteins•FRIL inhibits influenza virus entry by sequestering virions in late endosomes•Intranasal administration of FRIL protects against lethal H1N1 challenge in mice Liu et al. demonstrate that FRIL, a plant lectin isolated from the hyacinth bean, has potent antiviral activity against SARS-CoV-2 and diverse influenza virus strains. FRIL is effective in vivo against H1N1. FRIL’s antiviral activity is mediated by binding to complex-type N-glycans on viral glycoproteins, interfering with viral entry.